GAMBARAN KLINIKOPATOLOGI KARSINOMA PAYUDARA PADA WANITA USIA MUDA DI RSUP DR. M. DJAMIL PADANGTAHUN 2019-2021 - Meimonita, Dhitia; Intan, Shinta Ayu; Myh, Etriyel (EMPIRIS : Jurnal Sains, Teknologi dan Kesehatan, 2025)
Breast cancer is a disease that is often found in women characterized by the growth of abnormal cells in the breast. Age factor in breast cancer in young women is known to have a poor prognosis. The purpose of this study was to determine the clinicalpathological description of breast carcinoma in young women at Dr. RSUP. M. Djamil Padang year 2019-2021. This is a descriptive research with a total sampling technique using secondary data in the form of medical records. The sample of this study was young female breast carcinoma patients in 2019-2021.The results showed that the age range for breast carcinoma in young women was 41-45 years (44.3%), most of the histopathological types were invasive ductal carcinoma (62.5%), with the majority of histopathological grade II (60.2%), tumor location was mostly in the upper lateral quadrant (60.2%), with the most tumor size T2 (52.3%). The conclusion of this study is that most cases of breast carcinoma in young women at Dr. M. Djamil Padang Year 2019-2021 are at a high degree so that early detection is needed in cases of breast carcinoma in women at this young age